Handwriting: This handwriting of Tuan Guru Nik Abdul Aziz is appears to be a statement or request related to a personal matter, possibly regarding documents, travel, or an administrative issue - Nik Abdul Aziz Nik Mat
The handwriting concludes with a note about reviewing the situation with a signature and a phrase expressing trust in God's will ("Insha’Allah").